Targeted Terminal Deletions as a Tool for Functional Genomics Studies in Plasmodium - Pace, Tomasino; Scotti, Raffaella; Janse, Chris J.; Waters, Andrew P.; Birago, Cecilia; Ponzi, Marta (Genome Research, 2000)
We describe a transfection system that induces terminal deletions at specific chromosome ends in malaria parasites using a linear construct containing telomeric repeats at one end and plasmodial sequences able to drive homologous recombination at the other. A site-specific deletion was generated at one extremity of chromosome 5 ofPlasmodium berghei, which was stably maintained in the parasite population selected after transfection. The telomeric repeat array introduced with the construct reached the average length observed in natural telomeres of Plasmodium, indicating that in vivo telomere addition occurred at the newly formed extremity. The expression of a mutant dhfr/ts gene conferring pyrimethamine resistance, used as a selectable marker, was not affected by the proximity to the telomeric sequences, either in the presence or absence of drug pressure. In addition, no transcriptional silencing was observed on insertion of the mutant dhfr/ts gene either in subtelomeric or internal positions that are transcriptionally silent in blood-stage parasites. This suggests that the activity of its promoter is not affected by the chromatin organization of the chromosomal context.